An endoscopic treatment strategy for superficial tumors in patients with ulcerative colitis. Issue 2 (27th August 2020) - Nishio, Masafumi; Hirasawa, Kingo; Ozeki, Yuichiro; Sawada, Atsushi; Ikeda, Ryosuke; Fukuchi, Takehide; Kobayashi, Ryosuke; Makazu, Makomo; Sato, Chiko; Kunisaki, Reiko; Maeda, Shin
Abstract: Background and Aim: Endoscopic resection is feasible for superficial tumors in patients with ulcerative colitis; however, endoscopic resection options have not been evaluated comprehensively. We evaluated the efficacy and safety of endoscopic submucosal dissection and endoscopic mucosal resection, and decision making regarding endoscopic resection options for patients with ulcerative colitis. Methods: Endoscopically treated tumors from patients with ulcerative colitis were analyzed retrospectively. We evaluated en bloc and R0 resection, adverse events, local tumor recurrence, and metachronous lesion occurrence rates. Results: We examined 102 tumors (mean size, 12 mm; non‐polypoid, 55 tumors) from 74 patients with ulcerative colitis, of whom, 39 and 63 underwent endoscopic submucosal dissection and endoscopic mucosal resection, respectively. The R0 resection rate was significantly higher for endoscopic submucosal dissection (97%) than for endoscopic mucosal resection (80%) ( P  = 0.0015). For 11–20‐mm tumors, the R0 resection rate was significantly higher for endoscopic submucosal dissection (94%) than for endoscopic mucosal resection (55%) ( P  = 0.0027); the endoscopic submucosal dissection and endoscopic mucosal resection R0 rates did not differ for ≤ 10‐mm tumors. The non‐polypoid tumor R0 resection rates were significantly higher for endoscopic submucosal dissection (100%) than for endoscopic mucosal resection (65%) ( P  < 0.001) and did not differ regarding the polypoid tumor R0 resection rates (75% vs 86%, P  = 0.49). Four patients experienced intraoperative perforation during endoscopic submucosal dissection. No local recurrences occurred. Metachronous high‐grade dysplasia occurred in three patients during surveillance. Conclusions: In patients with ulcerative colitis, endoscopic submucosal dissection is suitable for ≥ 11‐mm and non‐polypoid tumors, whereas endoscopic mucosal resection is acceptable for ≤ 10‐mm tumors.